Contact Pressure Distribution During the Polishing Process of Ceramic Tiles: A Laboratory Investigation - A. S. A., Sani; F. J. P., Sousa; Zamzuri, Hamedon; Azmir, Azhari (IOP Publishing, 2016)
During the polishing process of porcelain tiles the difference in scratching speed between innermost and peripheral abrasives leads to pressure gradients linearly distributed along the radial direction of the abrasive tool. The aim of this paper is to investigate such pressure gradient in laboratory scale. For this purpose polishing tests were performed on ceramic tiles according to the industrial practices using a custom-made CNC tribometer. Gradual wear on both abrasives and machined surface of the floor tile were measured. The experimental results suggested that the pressure gradient tends to cause an inclination of the abraded surfaces, which becomes stable after a given polishing period. In addition to the wear depth of the machined surface, the highest value of gloss and finest surface finish were observed at the lowest point of the worn out surface of the ceramic floor tile corresponding to the point of highest pressure and lowest scratching speed.